PENGLIBATAN KOMUNITI DALAM PROGRAM PEMULIHAN REMAJA HAMIL LUAR NIKAH DI RUMAH PERLINDUNGAN TERPILIH: Community Involvement in the Rehabiliation Programme of Unmarried Pregnant Teenagers at Selected Shelter Home - Valaitham, Sumitra; Abdullah, Raihanah; Mansor, Nurul Husna; Fitriani, Wahidah (Jurnal Syariah, 2024)
The community plays a crucial role in changing and shaping the behaviour of unmarried pregnant teenagers. Research indicates that these teenagers often face social exclusion because their actions are seen as violations of community norms, leading to their placement in protective institutions to conceal pregnancy. This study focuses on the community's role in aiding the behavioral treatment of adolescents in shelters, specifically Darul Wardah (DARWA) Shelter in Selangor, Pusat Jagaan Baitus Solehah (BS) in Johor, and Generasiku Sayang (GKS) in Kelantan.The main objective of this study is to explore the impact of community involvement in the rehabilitation programs at these shelters and to suggest ways to enhance this involvement. A qualitative approach was employed, utilising a multiple case study design and semi-structured interviews to analyse community involvement in recovery programs for pregnant teenagers in selected shelters. The participants of this study consisted of two groups: (a) six shelter residents, and (b) four authority figures, including managers and counsellors. The findings revealed that the three shelters had various community programs involving families, neighbourhoods, and stakeholders, such as the Institute of Higher Education and the Ministry of Health. However, there is a notable gap in parental involvement and direct support to meet the needs of youth.